PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN PIUTANG, RASIO LIKUIDITAS, DAN PENJUALAN PRODUK LOGAM MULIA TERHADAP PROFITABILITAS PT PEGADAIAN PURWOTOMO SURAKARTA - Rispantyo, Lani Hayati, Djoko Kristianto & (Universitas Slamet Riyadi, 2016)
The purpose of this study was to analyze the effect of working capital turnover, accounts receivable turnover, liquidity ratios and sales of precious metal products on profitability partially and simultaneously. This research is a case study in PT Pegadaian Purwotomo Surakarta. Source data used are secondary data is data in the form of annual financial statements that are used PT Pegadaian Purwotomo Surakarta at year 2011 – 2015. Data collection used secondary data through documentation. Data were analyzed used multiple linear regression. The results showed that the working capital turnover has positive and significant effect on profitability. Accounts receivable turnover has negatif but no significant effect on profitability. The liquidity ratio has negative but no significant effect on profitability. Sales of precious metal products has positive and significant effect on profitability. Working capital turnover, accounts receivable turnover, liquidity ratios and sales of precious metal products has simultaneously effect on profitability.Keywords: Working capital turnover, accounts receivable turnover, liquidity, sales of precious metal products and profitability.